Beyond weight loss: Impact of a weight management programme for mid‐older Australians in private health insurance. Issue 3 (26th March 2020) - McGill, Bronwyn; Bauman, Adrian; Phongsavan, Philayrath; Grunseit, Anne C.; Lees, Dominic; Shepherd, Leah; Lawler, Luke; O'Hara, Blythe J.
Summary: Weight‐loss maintenance and lifestyle behaviour necessary to manage weight are undisputedly challenging. We evaluated a secondary prevention weight‐loss maintenance programme for participants (n = 490) with weight‐related chronic disease in the Australian private health insurance setting. This study investigated the impact of the maintenance programme on anthropometric and lifestyle risk behaviour changes after 6 and 12 months, and trends in weight‐loss maintenance after 1 year. Using a pre‐ and post‐test design, data were analysed with generalized linear mixed models for repeated measures to determine the effect of the programme on weight loss and lifestyle behaviour outcomes. After initially losing a clinically significant amount of weight (mean 9.1 kg), maintenance‐programme participants maintained clinically significant weight loss (mean 7.6 kg) at 12 months. Rates of discontinuation in the programme were high (47% at 6 months and 73% at 12 months). Weight‐loss maintenance was achieved by 76% of participants at 3 months and 62% at 6 months, stabilizing at 55% and 56% at 9 and 12 months, respectively. Greater initial weight loss was associated with weight‐loss maintenance at 12 months. Participants <55 years demonstrated consistent weight‐loss maintenance over this time but the odds for successful weight‐loss maintenance for those ≥55 years continued to decrease over time. At maintenance‐baseline, 68.3% of participants had sufficient physical activity for health; 61.4% and 19.8% met recommended fruit and vegetable consumption, respectively. All lifestyle risk behaviours were maintained at 12 months. A programme extending support strategies for maintaining weight‐related behaviour shows promise to successfully support these changes over 12 months. There is a potentially important opportunity for targeted intervention at 6 to 9 months.